2003
DOI: 10.1677/jme.0.0300087
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin-releasing hormone receptors -- similarities and differences

Abstract: Thyrotropin-releasing hormone (TRH) initiates its effects by interacting with cell-surface membrane

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
131
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 58 publications
2
131
0
3
Order By: Relevance
“…It is also recognized that TRHR2 is not present in humans (Gloriam et al, 2007;Sun et al, 2003). We also confirmed independently using the blastp algorithm [http://blast.ncbi.nlm.nih.gov/] that no ortholog exists in human for mouse or rat TRHR2.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 73%
See 3 more Smart Citations
“…It is also recognized that TRHR2 is not present in humans (Gloriam et al, 2007;Sun et al, 2003). We also confirmed independently using the blastp algorithm [http://blast.ncbi.nlm.nih.gov/] that no ortholog exists in human for mouse or rat TRHR2.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 73%
“…Two G Protein-Coupled Receptor (GPCR) subtypes, designated TRHR1 and TRHR2, have been identified to date in mediating TRH actions in non-human mammalian species (Cao et al, 1998;Itadani et al, 1998;Sun et al, 2003). Recent knock-out studies in mouse indicated that TRHR2 receptors account for no more that 5% of total binding in brain and that the CNS effects of TRH and TRH analogs were lost in mice in which TRHR1 was deleted (Thirunarayanan et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Inactivation of TSHR declines the thyroglobulin gene expression by the arbitration of c-AMP and concentration of thyroid hormones. Moreover, it belongs to G Protein Coupled Receptor (GPCR) family (Sun et al 2003) which found on surface of the cell membrane whereas thyroid receptor is a nuclear receptor. This means that targeting TSHR is less cumbersome as compared to thyroid receptor for drug molecules (Schapira et al 2003) and makes the bioavailability of drug for TSHR as compare to thyroid receptor.…”
Section: Simulation Analysis Of the Constructed Modelmentioning
confidence: 99%